Formation of Starch–Lipid Complexes during the Deep-Frying Process and Its Effects on Lipid Oxidation - Hu, Xueying; Li, Zhaoyang; Wang, Fengyan; Mu, Hongyan; Guo, Liping; Xiao, Junxia; Liu, Yuanfa; Li, Xiaodan (Foods, 2022)
In the present study, maize starch (MS), potato starch (PS), high-amylose maize starch (HAMS), and wheat starch (WS) were deep-fried in soybean oil that was continuously heated for 40 h under 180 °C. The thermodynamic and pasting properties of deep-fried starch samples were determined. The results suggested that starch–lipid complexes formed with the extension of frying oils’ usage; however, their number was not dependent on the frying oils’ life cycle. Importantly, the results of pasting properties revealed the following strength of intermolecular force in deep-fried starch samples: PS > MS > HAMS > WS. The results of XRD and FTIR analysis confirmed the formation of starch–lipid complexes during the deep-frying process. Furthermore, the results of the in vitro digestibility of deep-fried starch revealed that the formation of starch–lipid complexes inhibited the swelling of starch granules and prevented the entrance of amylase into the interior. Additionally, the results of the oxidation stability of deep-frying oil indicated that the formation of starch–lipid complexes did not alter the trend of lipid oxidation as an effect of the limited number of starch–lipid complexes. These results could have critical implications for the development of healthier deep-fried foods.